2004
DOI: 10.1084/jem.20040342
|View full text |Cite
|
Sign up to set email alerts
|

Masking of Phosphatidylserine Inhibits Apoptotic Cell Engulfment and Induces Autoantibody Production in Mice

Abstract: Apoptotic cells are rapidly phagocytosed by professional phagocytes, such as macrophages and dendritic cells. This process prevents the release of potentially noxious or immunogenic intracellular materials from dying cells, and is thought to play a critical role for the maintenance of normal functions in surrounding tissues. Milk fat globule-EGF-factor 8 (MFG-E8), secreted by activated macrophages and immature dendritic cells, links apoptotic cells and phagocytes, and promotes phagocytosis of apoptotic cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
214
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(216 citation statements)
references
References 40 publications
1
214
1
Order By: Relevance
“…MFG-E8 is a bridging molecule that stimulates phagocytosis of apoptotic cells through specific binding to PS on apoptotic cells via COOH-terminal factor VIII homologous domain and to avb3 integrin expressed on phagocytes via an NH 2 -terminal EGF-like domain. 88 They have shown that coexpression of MFG-E8 inhibits vaccination activity of irradiated GM-CSF-secreting tumor cells in the B16 melanoma model, whereas an MFG-E8 mutant potentiates GM-CSF-induced tumor destruction. 87 Interestingly, this MFG-E8 mutant retains the capacity to bind PS on apoptotic cells but contains a modified integrin-binding domain that inhibits phagocytosis of apoptotic cells.…”
Section: Exploitation Of Molecules On the Surface Of Dying Cells For mentioning
confidence: 99%
See 1 more Smart Citation
“…MFG-E8 is a bridging molecule that stimulates phagocytosis of apoptotic cells through specific binding to PS on apoptotic cells via COOH-terminal factor VIII homologous domain and to avb3 integrin expressed on phagocytes via an NH 2 -terminal EGF-like domain. 88 They have shown that coexpression of MFG-E8 inhibits vaccination activity of irradiated GM-CSF-secreting tumor cells in the B16 melanoma model, whereas an MFG-E8 mutant potentiates GM-CSF-induced tumor destruction. 87 Interestingly, this MFG-E8 mutant retains the capacity to bind PS on apoptotic cells but contains a modified integrin-binding domain that inhibits phagocytosis of apoptotic cells.…”
Section: Exploitation Of Molecules On the Surface Of Dying Cells For mentioning
confidence: 99%
“…87 Interestingly, this MFG-E8 mutant retains the capacity to bind PS on apoptotic cells but contains a modified integrin-binding domain that inhibits phagocytosis of apoptotic cells. 87,88 A possible explanation for this anti-tumor effect may be that the MFG-E8 mutant inhibits the clearance of irradiated apoptotic tumor cells by masking PS on apoptotic cells, which then become secondary necrotic cells thereby enhancing immunogenecity. These findings suggest that shielding of PS on apoptotic cells by mutant MFG-E8 or annexin-V together with the adjuvant activity of GM-CSF may provide a novel combined anti-tumor strategy.…”
Section: Exploitation Of Molecules On the Surface Of Dying Cells For mentioning
confidence: 99%
“…Injection of mutant MFG-E8 (engineered to mask PS and reduce apoptotic cell uptake) also elicits autoimmune responses, particularly when administered along with apoptotic cells. 29 Since apoptotic cells are considered the original antigenic insult, the consequences of the early autoimmune response to surface components on such cells assume obvious importance. It is probable that both the nature of the antigens recognized as well as the nature of the elicited antibodies and their downstream biological effects could influence the future course of disease.…”
Section: Reactivity Of the Immunizing Antibody (Rn86) Is Shown For Rementioning
confidence: 99%
“…24 Others have speculated that PS molecules on viable cells could somehow be masked, and unavailable for recognition by macrophages. 11 However, masking of externalized PS in vivo by administration of a mutant form of MFG-E8 was recently found to trigger autoantibody production in mice, 25 making this an unlikely explanation. On the other hand, it is conceivable that viable cells could express other, dominant signals that discourage engulfment in spite of PS externalization.…”
Section: Emerging Roles For Ps Signaling In Nonapoptotic Cellsmentioning
confidence: 99%